Praktische technische Kompetenzen im Techniklehramt - Ermel, Dorothee; Riese, Josef (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020. Essen: Universität Duisburg-Essen)

Digitale Kompetenzen im Techniklehramt - Albert, Gerrit; Riese, Josef (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020. Essen: Universität Duisburg-Essen)

Entwicklung der Fähigkeit zur Unterrichtsplanung im Fach Physik - Schröder, Jan; Vogelsang, Christoph; Riese, Josef (Naturwissenschaftlicher Unterricht und Lehrerbildung im Umbruch? Gesellschaft für Didaktik der Chemie und Physik. Online Jahrestagung 2020)

Service life estimation of self‐piercing riveted joints by linear damage accumulation - Masendorf, Lukas; Wächter, Michael; Esderts, Alfons; Otroshi, Mortaza; Meschut, Gerson (Fatigue & Fracture of Engineering Materials & Structures)

Correlation bound for a one-dimensional continuous long-range Ising model - Hasler, David; Hinrichs, Benjamin; Siebert, Oliver (Stochastic Processes and their Applications)
We consider a measure given as the continuum limit of a one-dimensional Ising model with long-range translationally invariant interactions. Mathematically, the measure can be described by a self-interacting Poisson driven jump process. We prove a correlation inequality, estimating the magnetic susceptibility of this model, which holds for small norm of the interaction function. The bound on the magnetic susceptibility has applications in quantum field theory and can be used to prove existence of ground states for the spin boson model.

Into the Woods: Experiences from Building a Dataflow Analysis Framework for C/C++ - Schubert, Philipp; Hermann, Ben; Bodden, Eric; Leer, Richard (SCAM '21: IEEE International Working Conference on Source Code Analysis and Manipulation (Engineering Track))

Modeling the Effects of Global Variables in Data-Flow Analysis for C/C++ - Schubert, Philipp; Sattler, Florian; Schiebel, Fabian; Hermann, Ben; Bodden, Eric (2021 IEEE 21st International Working Conference on Source Code Analysis and Manipulation (SCAM))

High Modulation Efficiency Segmented Mach-Zehnder Modulator Monolithically Integrated with Linear Driver in 0.25 \textmum BiCMOS Technology - Kress, Christian; Singh, Karanveer; Schwabe, Tobias; Preußler, Stefan; Schneider, Thomas; Scheytt, J. Christoph (OSA Advanced Photonics Congress 2021)
We present a monolithically integrated electronic-photonic Mach-Zehnder modulator with a linear, segmented driver on the same silicon substrate. As metric for the modulation efficiency, the external V$π$ is hereby reduced to only 420 mV.
Keywords: Analog to digital converters; Extinction ratios; Grating couplers; Modulation; Modulators; Phase shift

Analysis of the effects of jitter, relative intensity noise, and nonlinearity on a photonic digital-to-analog converter based on optical Nyquist pulse synthesis - Kress, Christian; Bahmanian, Meysam; Schwabe, Tobias; Scheytt, J. Christoph (Opt. Express)
An analysis of an optical Nyquist pulse synthesizer using Mach-Zehnder modulators is presented. The analysis allows to predict the upper limit of the effective number of bits of this type of photonic digital-to-analog converter. The analytical solution has been verified by means of electro-optic simulations. With this analysis the limiting factor for certain scenarios: relative intensity noise, distortions by driving the Mach-Zehnder modulator, or the signal generator phase noise can quickly be identified.
Keywords: Analog to digital converters; Diode lasers; Laser sources; Phase noise; Signal processing; Wavelength division multiplexers

Governance and Reputation in the Market for Experience Goods - Fanasch, Patrizia